ENGLISH LOANWORDS IN USING COMMUNITIES IN JAMBESARI VILLAGE, GIRI DISTRICT, BANYUWANGI - Imam Mahdiyono; Syamsul Anam; Agung Tri Wahyuningsih (Fakultas Ilmu Budaya Universitas Jember, 2014)
In this paper, we present an analysis of English loanwords that are spoken by the people of Jambesari villagethat are regarded as their own language. The loanwords also experience some deviations. The term 'loanword'can be defined as a word adopted from another language with little or no modification. As asserted by Methamand Hudson (1969:482) that loanwords are words which have been taken over by one language from anotherand they represent only one phenomenon in the wider context of language contact. This study aims to know theway people got the English loanwords, to know where people use the English loanwords, and to know thechanges of the English loanwords. It can be analyzed by using the concept of language contact and languagechange. The analysis is conducted by using descriptive method. The result shows that people got the Englishloanwords from other people. They also use the English loanwords everywhere according to the context ofsituation. Then, the alterations occur in the kind of pronunciation, spelling, word class, and meaning.Keywords: Loanword, language contact, language change.